Analysis of Inflation, Regional Gross Domestic Product and Minimum Wage on Employment Absorption in East Nusa Tenggara Province - Rahmatullah, Muhammad Zidan Al Aziz; Marseto, Marseto (PT. Riset Press International, 2024)
Based on observations of phenomena in the East Nusa Tenggara Province, this region demonstrates significant progress across various sectors such as tourism, education, and industry, supported by increases in minimum wages, constant domestic economic growth (constant GDRP), and relatively low inflation rates. However, this situation has not successfully optimized labor absorption. This study aims to examine the